Posttranslational processing of methyl-accepting chemotaxis proteins in Escherichia coli - Sherris, David (1981)
Methyl-accepting chemotaxis proteins (MCPs) of Escherichia coli undergo changes in methylation state in response to chemical stimuli. The addition of methyl groups to MCP is dependent on cheR function; their removal is dependent on cheB function. This MCP methylation system is instrumental in establishing the unstimulated swimming pattern of E. coli and in enabling the cell to carry out sensory adaptation after a chemotactic response. We employed electrophoresis in sodium dodecyl sulfate-containing polyacrylamide gels to analyze MCP molecules synthesized in cheR deletion mutants lacking MCP-specific methyltransferase activity. MCP made under these conditions proved to be completely devoid of methyl groups. In the absence of cheB function as well, this unmethylated MCP is made in a form, designated 2(*), that exhibits several properties characteristic of methylated MCP. In the presence of cheB function, MCP 2(*) is processed to a form, designated 1(*), that no longer resembles methylated MCP. The rate of this conversion process is modulated by chemotactic stimuli. Both MCP 1(*) and MCP 2(*) are capable of initiating changes in flagellar rotation in response to stimuli, and, in the presence of cheR function, both forms can accept methyl groups. We suggest that MCP 2(*) is a normal intermediate in MCP synthesis in which one or more of the methyl-accepting glutamic acid residues carry a methyl-ester-like modification, which, like glutamic acid methyl esters, can be removed by cheB function. This cheB-dependent processing event does not appear to be reversible, but nevertheless it may play an important role in modulating the signaling behavior of newly synthesized MCP molecules.